2022
DOI: 10.4314/ejst.v15i3.4
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and feed utilization of Hubbard Classic chickens fed on boiled and sundried mango (Mangifera indica Linn.) seed kernel

Abstract: An investigation was undertaken to study the effects of feeding boiled mango seed kernel (BMSK) on the growth performance and feed utilization parameters of Hubbard broiler chicks with the objective of recommending the optimum level of mango seed kernel inclusion in broiler feed. The experiment was arranged in a completely randomized design with four treatments, each replicated three times with 13 birds each. One-hundred fifty-six-day-old chicks with uniform body weight (BW) were used and were distributed rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Beyene et al (2019) reported that mango kernels can replace maize entirely in laying hen diets, resulting in improved economic returns without impacting egg yield or quality parameters. Moreover, Beriso et al (2022) reported that incorporating up to 15% boiled mango kernel in Hubbard broiler diets can improve production performance and feed conversion parameters without adverse effects. Our results on nutrient content indicate the potential of the CLUK blend as a feedstuff is controversial for poultry nutrition due to the high ADF and NDF percentages in the CLUK blend.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyene et al (2019) reported that mango kernels can replace maize entirely in laying hen diets, resulting in improved economic returns without impacting egg yield or quality parameters. Moreover, Beriso et al (2022) reported that incorporating up to 15% boiled mango kernel in Hubbard broiler diets can improve production performance and feed conversion parameters without adverse effects. Our results on nutrient content indicate the potential of the CLUK blend as a feedstuff is controversial for poultry nutrition due to the high ADF and NDF percentages in the CLUK blend.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, because fruit residues, including shelled or unshelled kernels, are inexpensive, readily available, and include bioactive molecules, several studies have shifted to such residues as sources of antioxidants (Ibrahim et al, 2017;Jideani et al, 2021). Indeed, stone fruit kernels such as candlenut (Rohaida, 2014), grape (Karabacak et al, 2015), apricot (Orhangazi, 2017), date (Tareen et al, 2017), sour cherry (Gungor and Erener, 2020), and mango (Beriso et al, 2022) kernels have attracted great interest due to their potential for quality, healthy, cost-effective, and ecofriendly poultry production. All these studies have suggested that fruit processing by-products are effective and less expensive natural sources of bioactive compounds that exhibit significant antioxidant and synbiotic properties (Ibrahim et al, 2017;Jideani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Because MSK is less expensive than maize and even other feed ingredients, there may be less competition for cereals in general and maize in particular between humans and chickens. Using MSK as chicken feed would help the poultry industry cut production expenses associated with expensive conventional feed [32].…”
Section: Mango Seed Kernels (Mango Kernels)mentioning
confidence: 99%